User Behavior Traffi c Replay Technology for Space-IntegratedGround Information Network Based on Profi le Analyzing - Qingsong XUE; Xiaofeng WANG (天地一体化信息网络)
Faced the needs of user behavior emulation of the space-integrated-ground information network with complex behaviors and diverse protocols, an architecture based on cloud computing and virtualization technologies for replaying user behavior traffi c in the spaceintegrated-ground information network was designed.Furthermore, a user behavior traffi c automatic analysis and traffi c profi le generation technology based on deep packet inspection, and a user behavior traffi c replay technology of the space-integrated-ground information network based on traffi c profi le were researched, to achieve unifi ed, automated, and realistic simulation of miscellaneous kinds of user behavior traffi c.An emulation scenario of a space-integrated-ground information network with 6 space-based backbone network satellites and 66 space-based access network satellites was constructed.The experimental verifi cation of protocol traffi c profi le generation and traffi c replay of the broadband user behavior and narrow-band user behavior showed that the emulation of diversifi ed user interaction behaviors could provide eff ective support for the emulation of the space-integrated-ground information network.